VARIASI TANAMAN AIR SEBAGAI MEDIA UNTUK PERTUMBUHAN CACING SUTRA (Tubifex sp.) DENGAN SISTEM RESIRKULASI AIR - Asma, Yunita; Herliwati, Herliwati; Fauzana, Noor Arida (EnviroScienteae, 2023)
Silk worms is very popular and effective feed for fish larvae or fish seeds because of their high nutritional value such as protein, fat, minerals, vitamin B12, amino acids and unsaturated fats to fulfill the nutritional needs for the growth of fish seeds. This study aims to analyze the differences in water plants as a media cultivation silk worm to the growth of silk worms and to analyze water plants suitable as a media for silk worm that is able to provide high growth. This study used a completely randomized design (CRD) using 5 treatments and 3 repetitions, that is treatment A 100% mud, treatment B 50% mud + 50% apu wood, treatment C 50% mud + 50% kiambang, treatment D 50% mud + 50% water hyacinth and treatment E 50% mud + 50% genjer. The results of the study, treatment C 50% mud + 50% kiambang is the best for growth in long and weight of biomass. The results of the analysis of water quality are still in the optimal range for silk worm cultivation: 26,5oC-26,5oC, DO 2,50-4,32 mg/L, pH 6,19-6,11 dan ammonia 0,01mg/L.